Epitranscriptomic control of cancer immunity and therapy resistance - Zhao, Xingsen; Guan, Suhua (Frontiers in Immunology, 2025)
Epitranscriptomics, the study of dynamic chemical modifications on RNA mediated by “writers,” “erasers,” and “readers,” has emerged as a pivotal discipline in elucidating the intricate interplay between cancer and immune regulation. These reversible modifications (e.g. m6A, m5C, Ψ) govern RNA metabolism, stability, and translation, thereby exerting spatiotemporal control over immune cell differentiation, activation, and function. Dysregulation of RNA-modifying proteins disrupts immune surveillance, enhances tumor cell survival under stress, and promotes chemoradiotherapy resistance by altering RNA splicing, translation, and stress adaptation pathways. This review summarized the recent progress in the regulatory mechanisms profoundly influencing the tumor microenvironment (TME), modulating immune checkpoints, antigen presentation pathways, and the activity of immune cells. Furthermore, we discussed the therapeutic strategies and challenges in targeting epitranscriptomic regulators and epitranscriptomic editing technologies to enhance anti-tumor immune responses and overcome therapeutic resistance.